Operando UV–Vis diffuse reflectance spectroscopy insights into the methane dehydroaromatization reaction over Mo/H-ZSM-5 catalysts - Haben, Sebastian; Kromwijk, Josepha J.G.; Vollmer, Ina; Weckhuysen, Bert M. (Journal of catalysis, 2024)
[Display omitted] •Operando UV–Vis diffuse reflectance spectroscopy and chemometrics could distinguish the reaction phases of the methane dehydroaromatization process.•Upon activation in CO, the spectral component for the activation phase was removed.•During the active period, typical hydrocarbon pool intermediates could be observed.•Deactivation is governed by the built-up of polyaromatic coke species.•Catalyst preparation only impacts the dispersion of the molybdenum active phase, but not the spectral components. Methane Dehydroaromatization (MDA) is proposed as a possible way to valorize stranded natural gas, e.g., arising during crude oil drilling. In this study, we used operando UV–Vis Diffuse Reflectance Spectroscopy (DRS) in combination with Multivariate Curve Resolution Alternating Least Squares (MCR-ALS) to distinguish the MDA reaction phases of activation, induction, and deactivation. We identified three spectral components, which describe these distinct reaction phases. When the catalyst was activated in CO, two spectral components alone sufficiently described the operando UV–Vis DRS data. We further found that the preparation method of the Mo/ZSM-5 catalyst has little influence on the observed spectral features. However, the different preparation methods impact the dispersion of Mo, resulting in faster deactivation for the catalyst with more Mo-clusters compared to the catalyst with a higher Mo dispersion. This study shows that operando UV–Vis DRS in combination with the MCR-ALS methodology is a powerful analytical tool to disentangle and study the three MDA reaction phases.